Anti-Crisis Urban Design and Hotel Infrastructure: A New Paradigm of Post-War Urban Development - Bovsh, Liudmyla; Rasulova, Alla; Hopkalo, Larysa (Urban Planning and Construction, 2025)
This study investigates models for restoring hotel infrastructure within a comprehensive framework of crisis-responsive urban design during and after military aggression, using Ukraine as a focal case. By integrating restorative construction, inclusive urban design principles, and community participation, resilient cities aim to create environments that accommodate individuals with diverse mobility levels and needs. In the context of reconstructing Ukrainian cities, hotel infrastructure emerges not only as an economic asset but also as a critical component of an anti-crisis urban system capable of supporting social stability, mobility, and the economic revitalization of affected territories. The article advances a conceptual framework for crisis-oriented urban design that positions hotels as catalysts of spatial and social regeneration within the urban fabric. Drawing on theories of urban design, crisis management, and urban infrastructure, as well as international examples of post-disaster urban rehabilitation, the study demonstrates how innovative planning paradigms can facilitate the transformation of devastated or degraded urban areas. Particular attention is devoted to the role of hotel facilities in establishing temporary hubs for internally displaced persons, entrepreneurial activity, and educational and cultural initiatives that strengthen social interaction and local resilience. The paper further examines the challenges of post-war reconstruction through the lenses of urban policy, economic feasibility, and sustainable development principles. The findings indicate that crisis responsive urban design incorporating hotel infrastructure constitutes a new paradigm for post-war urban development—one capable of enhancing flexibility, viability, and social cohesion in contemporary Ukrainian cities.